The Effect of Atractylodes lancea (Thunb.) DC. on the Notch Signaling Pathway - Vindvamara, Ethan; Chaijaroenkul, Wanna (Journal of Basic and Applied Pharmacology, 2023)
Cholangiocarcinoma (CCA) is a cancer of the bile ducts and liver with a low survival rate. Development and progression of the disease involve many changes to gene expression including to genes involved in Notch signaling. The Notch signaling pathway is a highly conserved pathway that regulates differentiation, proliferation, and apoptosis among other things, mediated through direct cell-to-cell contact, and is implicated in many kinds of cancer including CCA. Atractylodes lancea (Thunb.) DC. (AL) is a plant used in traditional Thai medicine that has been shown to have anti-CCA activity. In this study, Notch pathway gene expression was analyzed from venous blood samples taken from Thai patients with advanced-stage CCA participating in a phase II clinical trial. Patients were given either standard palliative treatment (control) or oral capsule pharmaceutical formulation of standardized crude ethanolic AL extract with a daily dose of 1,000-1,500 mg. In total, 15 patients were included in the study. Twenty-four genes were analyzed for differential gene expression using nCounter® Analysis System, NanoString Technology and data was analyzed by performing fold change analysis. Patients’ gene expression on day 28 of treatment was compared against day 1 of treatment (baseline) for each treatment group. Data analysis revealed 20 genes had a significant fold change in expression from day 1 to day 28. Of these 20 genes, 7 genes had a significant fold change in expression in two treatment groups (DLL4, DTX4, HES1, HES5, HDAC1, APH1B, and LFNG), and 2 genes had a significant fold change in all three treatment groups (JAG1 and CREBBP). In conclusion, oral administration of standardized crude ethanolic AL extract affects expression of Notch signaling pathway-related genes in CCA patients; most notably, JAG1 expression was down-regulated in response to AL treatment, in a dose-dependent manner.